As experiências emocionais do gestor escolar na mediação de conflitos no cotidiano de sua atuação profissional - Costa, Maria do Socorro Moura (2022)
This study aims to understand the emotional experiences lived by the school manager on the mediation of conflicts in his or her professional performance. The objective of the thesis is based on the following assumptions: (1) the conflicts that emerge in the daily life of school management lead the school manager to adopt mediation as a professional practice; (2) the school manager faces emotional experiences in the processes of school management that have implications for his or her professional performance and; (3) school management through mediation and the school manager’s emotional experiences help to resolve conflicts in the school environment. To achieve the purpose of the study, the following specific objectives were established: i) to identify the conflict mediation process experienced by the school manager in the daily school management; ii) to characterize the emotional experiences (triggered by situations of intra and extramural conflicts at school) experienced in the performance of the school manager; iii) to identify the implications of emotional experiences in the performance of the manager in the management by mediation and in the resolution of conflicts in the school space. This is an exploratory study, of a qualitative nature, with an interpretive ontological stance, anchored in the epistemological contribution of the social constructionist perspective of emotions and in the sociological perspective of the social construction of reality. The organizational field focused on were eleven municipal and state public schools, in the city of Teresina - PI, selected by the quality criterion of the official indexes of success and school permanence considered in the time lapse of nine years, where the performance of the management stands out. The empirical material analyzed resulted from in-depth qualitative interviews, carried out with the eleven managers of the selected schools, and the analysis was based on transcribed narratives, using the technique of content analysis, and the results made it possible the identification of facilitating and/or hindering management factors, which are linked to the emotional burden inherent within the scope of educational institutions. The main findings show the relationship between the school manager’s engaged leadership in conducting partnership with other members of the management team, teaching group, families and in the relationship with the surrounding community and with the Public Power. Reveal intuitive mediation exercised by school managers on the sidelines of the training he received was also revealed, as a result of the emotional processes of awareness/perception, regulation, creativity and activation. From a theoretical point of view, the study made possible new incursions to other educational levels, members of the management team, as well as the teaching staff. From the practical angle, the contribution of this study refers to the inclusion of new elements in courses already proposed by the respective Departments of Education, with the aim of leading school managers to understand how emotions can help in school management processes. In summary, the study revealed the reflective capacity of emotions in conflict situations and in the demand for mediation from the manager, as possible to generate knowledge and create repertoires that can be used in other contexts, enabling professional maturation, expressed in the elaboration of managerial strategies and in the taking of decisions.